Current Anti-Myeloma Chimeric Antigen Receptor-T Cells: Novel Targets and Methods - Ece Vural; Meral Beksaç (Balkan Medical Journal, 2025)
Multiple myeloma (MM) treatment becomes a major challenge once triple-class or penta-refractoriness develops. Emerging immunotherapies, including bispecific antibodies or chimeric antigen receptor (CAR)-T cell therapy, are promising options for such patients. However, the requirement for specialized expertise and staff under stringent manufacturing conditions results in high costs and restricted production. This article explores the manufacturing and clinical application of CAR T-cells in MM, highlighting their potential, limitations, and strategies to enhance efficacy. CAR-T can be manufactured by pharmaceutical companies or accredited academic centers authorized to produce and market gene-edited cellular products. This process includes sequential steps: T cell apheresis from the patient, selection of the cells, activation, gene transfer, expansion of the produced cells, cryopreservation, and reinfusion of the cells into a lymphodepleted patient. While CD3+ T cells are typically employed for CAR-T production in clinical studies, studies have demonstrated the potential advantages of specific T cell subgroups, such as naive, central memory, and memory stem cells, in enhancing efficacy. Following T cell harvesting, the subsequent phase involves genetic modification. CAR-T cells are frequently produced by applying viral vectors such as g-retrovirus or lentivirus. Although viral vectors are commonly used, non-viral methods-including CRISPR/Cas9 and integrative mRNA transfection methods produced by transposons-are also employed. Five different CAR-T cell generations have been developed. The myeloma-specific targets B-cell maturation antigen (BCMA), signaling lymphocyte activation molecular family 7, and G protein-coupled receptor class C group 5 member D are the most extensively studied in clinical trials. Emerging CAR-T cell targets under investigation include CD138, CD19, kappa light chain, CD56, NY-ESO-1, CD70, TACI, and natural killer G2D. In 2021, idecabtagene vicleucel, a BCMA-targeting agent, became the first CAR-T therapy approved for relapsed/refractory MM, marking a significant milestone in MM treatment. Subsequently, ciltacabtagene autoleucel has also been approved. However, CAR-T resistance is an emerging issue. Resistance mechanisms include T cell exhaustion, antigen escape (loss of BCMA), and tumor microenvironment-related inhibitors. To address these challenges, strategies such as BCMA non-targeted or dual-targeted CAR-T, memory T cells, humanized CAR-T, and rapidly manufactured PHE885 cells have been developed. To enhance specificity, ongoing investigations include bicistronic CAR/co-stimulator receptors, formation of memory-phenotype T cells, combination with immunomodulators or checkpoint inhibitors, armored CAR-T cells, cancer-associated fibroblast inhibitors, and CAR approaches that inhibit exhaustion signals. In conclusion, studies are exploring the use of CAR-T at an earlier stage, including at diagnosis, with an aim to replace ASCT. CAR-T has introduced a new dimension to MM treatment; however, limited efficacy in high-risk MM and the emergence of resistance to CAR-T remain key challenges to be addressed.